2017
DOI: 10.4172/2167-7700.1000235
|View full text |Cite
|
Sign up to set email alerts
|

Targeting MUC16 in Cancer Therapy

Abstract: Over the recent decades, there has been a number of studies investigating the role of mucins in the pathogenesis of various cancers such as breast, lung, ovarian, gastrointestinal and pancreatic malignancies. Since then, it has been discovered that mucins play a critical role in tumorigenesis as they can mediate cell proliferation, metastasis and resistance to chemotherapy. Thus, mucins have been explored as a potential therapeutic target as well as a biomarker, as cancer cells often have an aberrant expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…55 To our best knowledge, the presence of MUC6 has not been shown in the oral mucosa until now, whereby the expression of MUC16 in saliva samples of healthy patients and patients with oral squamous carcinoma showed no correlation to the prognosis as described by Suh et al (2017). 56 On the other hand, all samples expressed MUC1A, MUC1B, MUC3A, MUC15, MUC18, and MUC20. The expression of MUC1 in the buccal area and salivary glands has been described before.…”
Section: Discussionmentioning
confidence: 94%
“…55 To our best knowledge, the presence of MUC6 has not been shown in the oral mucosa until now, whereby the expression of MUC16 in saliva samples of healthy patients and patients with oral squamous carcinoma showed no correlation to the prognosis as described by Suh et al (2017). 56 On the other hand, all samples expressed MUC1A, MUC1B, MUC3A, MUC15, MUC18, and MUC20. The expression of MUC1 in the buccal area and salivary glands has been described before.…”
Section: Discussionmentioning
confidence: 94%
“…14 Nonetheless, MUC16 is known to modulate immune response to cancer. 6 Our gene set enrichment analyses also indicated that immune response, cell cycle checkpoints, and DNA replication and repair were significantly altered in GC samples with MUC16 mutations. Therefore, therapeutic regimens to abrogate immune inhibition, such as immune checkpoint blockade, may be beneficial for patients with GC who have MUC16 mutations.…”
Section: Discussionmentioning
confidence: 62%
“…5 MUC16 is a type I transmembrane mucin protein with 3 components: a C-terminal domain, a tandem repeat region, and an extracellular N-terminal section. 6,7 Cancer antigen 125 (CA-125), used to monitor disease progression in ovarian cancer, is part of the tandem repeat domain. 7 MUC16 (OMIM 606154) is one of the most frequently mutated genes in GC; however, its associations with TML and prognosis remainunclear.Inthisstudy,weinvestigatedwhetherMUC16mutations are associated with TML and prognosis in patients with GC.…”
mentioning
confidence: 99%
“…Because of the potency of a bispecific antibody, it is essential to identify a tumor target antigen with sufficient tumor selectivity to limit toxicity. Mucin 16 (MUC16) is a large integral membrane glycoprotein that is highly expressed in a number of epithelial cancers (16) but at low abundance in epithelial cells of several tissues including trachea, eye, and female reproductive organs, as well as the serosal epithelial lining of the peritoneal and thoracic cavity. MUC16 is thought to provide a barrier function in some of these organs (17,18).…”
Section: Introductionmentioning
confidence: 99%